Sistem Informasi Manajemen Arsip Surat Berbasis Desktop pada BP3TKI Jakarta - Wiji Lestari; Faiz Rafdhi (Jurnal CoSciTech (Computer Science and Information Technology), 2020)
At the BP3TKI Jakarta office, there are still some problems in processing incoming and outgoing letters including frequent double numbering errors in incoming and outgoing letters, relating to storage in this case archiving is only in the form of storing hardcopy documents which results in lost letters and a lot of use of paper so spend more in terms of company operations. So it was designed a Letter Filing Management Information System in Jakarta BP3TKI. In building a Letter Filing Management Information System in BP3TKI Jakarta using Vb.Net with visual studio 2010 software as a programming language and display design. MySQL as a database. This system development uses UML (Unfied Modeling Language) tools as an analysis of the running system. The research methodology uses a waterfall, with stages of analysis, design, manufacture, coding, testing. This study produces a Letter Archive Management Information System in BP3TKI Jakarta that can facilitate the management of incoming and outgoing mail data, the process of making reports, recording letters, storing letters properly so as to facilitate the search for data. Can change a manual mail archive management into a structured system.